Habitation: anthropocentric notions of home - Laugen, Melissa, author; Bates, Haley, advisor; Dineen, Mark, committee member; Kissell, Kevin, committee member; Ryan, Ajean, committee member (Colorado State University. Libraries, 2018)
One of the most essential human conditions is to seek and establish a home. Conceptualization of home is generated by the material and psychological structures impacted by our shared cultural ideals. The vernacular of the home extends beyond mere shelter and creates context for the discourse of identity. Our external selves are socially constructed and identified by our connection to an abode, a region, or an even larger territory….home. Concurrently, we have a need for a private realm, a space to conceal the personal and vulnerable parts of our existence. In the bodies of work, I reside, Armament, and Comforter, I have produced a system of structures that imply the fragility and strength of the fabric of the domicile. These objects exemplify an innate desire for the sanctuary, protection and comfort of the intimate interior and simultaneously reveal that there is imperfection and impermanence in the concept of the domestic.
Keywords: electroforming; home; sculpture; enamel; art; metalsmithing